Pengaruh Modal Intelektual terhadap Nilai Perusahaan dengan Economic Moat dan Kinerja Perusahaan sebagai Variabel Mediasi pada Perusahaan yang Terdaftar di BEI - Wedatama, Ceilio Marsa; Pratama, Vany Erdiyanti; Narsa, Niluh Putu Dian Rosalina Handayani (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to test the impact between intellectual resource and firm value with financial performance and economic moat as a mediasi variable. The population used is companies listed on kompas 100 index during 2015-2019 period, with a total sample of 147 samples according with certain criteria. This study uses path analysis and sobel test. The results of this study indicate that intellectual capital has a positive effect on firm value, intellectual capital has a positive effect on firm value through firm performance. However, economic moat is not proven to mediate the influence between intellectual capital and firm value.